PENGARUH RASIO PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PERUSAHAAN TRANSPORTASI PADA BURSA EFEK INDONESIA TAHUN 2018 – 2021 - Indah Eka Wahyuni; Samsul Bakri (Program Studi Manajemen Fakultas Ekonomi UST, 2023)
The purpose of this study is to determine the effect of profitability ratios, liquidity ratios and solvency ratios on the stock prices of transportation companies on the Indonesia Stock Exchange in 2018-2021. This research method uses an associative analysis technique with a quantitative approach. The population in this study are transportation companies on the Indonesia Stock Exchange in 2018-2021 totaling 141 companies. The sampling technique used non-probability sampling with purposive sampling method, so that the samples used were 11 companies. The data analysis method uses panel data regression by testing the F test and t test hypotheses, which first carried out the classical assumption test and selected the best model. The results obtained show that the profitability ratio proxied by return on equity and earnings per share, the liquidity ratio proxied by the current ratio and the solvency ratio proxied by the debt to equity ratio simultaneously affect the stock prices of transportation companies on the Indonesia Stock Exchange in 2018 -2021. Partially, return on equity has a negative and significant effect on stock prices, earnings per share has a positive and significant effect on stock prices, the current ratio has no significant effect on stock prices and the debt to equity ratio has no effect on stock prices of transportation companies on the Indonesia Stock Exchange 2018-2021.